Community participation in educational policy making: Views of education directorate officials - Jubran, Ali M.; Karasneh, Samih M. Al; Merah, Souad; Said, Afkar; Tahraoui, Ramdane; Qasimi, Aida Al (Edelweiss Applied Science and Technology, 2024)
This study has investigated the perceptions of regional education administration directors concerning the role and influence of community participation in educational policymaking in Jordan. The qualitative descriptive-analytical approach was adopted in this research to study the leadership with over 15 years of experience through semi-structured interviews. The findings reveal that school administrations largely permit only symbolic participation, as highlighted by 66.6% of respondents, while 58.4% expressed dissatisfaction with the Ministry’s efforts to ensure meaningful involvement. The study underscores the critical need to strengthen community engagement in shaping inclusive and equitable policies that address societal needs. It proposes strategies such as establishing advisory councils, fostering transparency, and promoting inclusiveness in decision-making processes. By contributing to global discussions on participatory governance, the research directly aligns with the United Nations Sustainable Development Goal No. 4, which advocates for inclusive and equitable quality education. The recommendations chart a clear course for achieving transformative educational reform not only in Jordan but also in similar global contexts.